Perbandingan Penghitungan Massa Tubuh Dengan Menggunakan Metode Indeks Massa Tubuh (IMT) dan Bioelectrical Impedance Analysis (BIA) - Wiranata, Yonathan; Inayah, Inayatul (STIKES Yayasan RS.Dr.Soetomo, 2020)
Anthropometric is a method of body mass composition calculation resulting either roughly or directly (detail). BMI is an anthropometric method performed by measuring body weight and height to classify one’s body mass index. BIA is an anthropometric methods used to asses body mass composition, including water mass, musculoskeletal, and mainly body fat mass. The purpose of this study isto find the relationship between the two methods of anthropometry and see the comparasion of body mass composition resulted by the two methods. Study design with descriptive analytics with cross sectional approach, the sampling technique use quota sampling, 41 respondents. Data analysis with analysis of Pearson correlation test (significance level α = 0.05, p – value < α). Results of a normal BMI of 25 respondents (61%), the results of normal BIA 29 respondents (71%) and fat mass between (from 11.00 to 37.30, the average 24.05). obtained a result of a positive relationship between BMI with the composition of body fat (r = 0.708, p <0.000). With it was found that BMI and body fat composition has a significant relationship (p <0.000). It can be cloncuded BMI has strong correlation with body fat mass that were measured by using the BIA method resulted from PSIK student at the University of Muhammadiyah Malang. BIA method is no better than BMI method as a parameter to determine body mass composition.Kata Kunci: Indeks Massa Tubuh, Bioelectrical Impedance Analysis, Komposisi Tubuh.